Knowledge and Perceptions of Agricultural Communications Pilot Curriculum in Arkansas Secondary Agricultural Classrooms - Carley Calico; Leslie D. Edgar; Don W. Edgar; Don M. Johnson (Journal of Applied Communications, 2014)
The purpose of this mixed-method study was to assess the effectiveness of agricultural communications curriculum developed and incorporated into a semester-long agricultural leadership and communications course for secondary agricultural education programs in Arkansas. Students (N = 297) participated in newly developed instructional modules addressing four categories of agriculture-themed curricula predetermined by a committee of agricultural education and communications faculty at the University of Arkansas (careers, writing, design, and multimedia). Student agricultural communications knowledge change was assessed using pre- and post-test instruments in each module of study. Additionally, content analysis of participating teachers’ journals was used to identify emergent themes related to teachers’ experiences teaching the curriculum throughout the semester. Overall, the findings from this study indicated students’ knowledge increased after instruction for each curriculum module: careers (16.2%), writing (23.1%), design (35.7%), and multimedia (31.3%). Lack of time, limited technology, teacher training, and curriculum content were the most common emergent themes among teachers. Based on findings from this study, it was concluded future efforts should be made to provide technology for agricultural education instructors to improve agricultural communications program effectiveness and reach.
Keywords: Agricultural communications; agricultural communications curriculum; pilot study; curriculum in secondary agricultural education programs; technology